International perspectives of festivals and events paradigms of analysis - Ali-Knight, Jane. (Advances in tourism research series., 2009)
International Perspectives of Festivals and Events addresses contemporary issues concerning the potential of festivals and events to produce economic, social, cultural and community benefits. Incorporating a range of international perspectives, the book provides the reader with a global look at current trends and topics, which have until now, been underrepresented by current literature. International Perspectives of Festivals and Events includes a broad range of research, case studies and examples from well-known scholars in the field, to form a unified volume which informs the reader of the current status of festivals and events around the world. In a fast-moving industry where new theory and practice is implemented rapidly, this is essential reading for any advanced student or researcher in festivals and events. * Provides a contemporary look at the current issues in the field * Expertly edited and contributed to by an international group of subject specialists * Advances and emphasises the interrelationship of multidisciplinary academic approaches, contexts and research methodologies in festivals and events.